Perspectives on learning disabilities: Biological, cognitive, contextual - Sternberg, R.J.; Spear-Swerling, L. (Taylor and Francis, 2018)
This book discusses biological, cognitive, educational, sociological, and interactive to discuss the nature of learning disabilities, its origins, its diagnosis, and effective remediation. It emphasizes the development of ideas as the motor forces behind the economic policies. © 1999 Taylor & Francis.
Journal Abbreviation: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual Pages: 296 Publication Title: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual
Keywords: dept.sed